Did U.S. consumers respond to the 2014-2015 oil price shock? Evidence from the consumer expenditure survey - Patrick Alexander; Louis Poirier (Bank of Canada, 2018)
The impact of oil price shocks on the U.S. economy is a topic of considerable debate. In this paper, we examine the response of U.S. consumers to the 2014-2015 negative oil price shock using representative survey data from the Consumer Expenditure Survey. We propose a difference-in-difference identification strategy based on two factors, vehicle ownership and gasoline reliance, which generate variation in exposure to oil price shocks across consumers. Our findings suggest that exposed consumers significantly increased their spending relative to non-exposed consumers when oil prices fell, and that the average marginal propensity to consume out of gasoline savings was above 1. Across products, we find that consumers increased spending especially on transportation goods and non-essential items.
Keywords: D12; E21; Q43; 330; Business fluctuations and cycles; Domestic demand and components; Recent economic and financial developments